Organizational and Work Psychology / Ian Rothmann, Cary Cooper - Rothmann, Ian
Organizational and Work Psychology examines individual behaviour, motivation and satisfaction, diversity management, teamwork, and decision making. Personnel practices and human resource management, performance management and career management are also explored in depth. The book includes discussions on health, wellness and dysfunctional behaviour at work, politics and power in organizations, leadership, job design and the meaning of work. It concludes with an analysis of organizational cultures and climates and organizational change and development.